การพัฒนาเครื่องมือวินิจฉัยและกิจกรรมปรับเปลี่ยนมโนทัศน์ที่คลาดเคลื่อนด้านการกำหนดปัญหาวิจัยทางการศึกษาสำหรับนิสิตบัณฑิตศึกษา - สรวีย์ ศิริพิลา (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Research misconception is a long-standing problem. If researchers have misconceptions in research problem formulation the first and important step of doing a research, the research problem formulation will be erroneous and mislead the rest of research steps. The purposes of this study were 1) to develop instruments for diagnosing misconceptions in educational research problem formulation, 2) to diagnose misconceptions in educational research problem formulation, and 3) to develop activities for correcting misconceptions in educational research problem formulation. The research was divided into 3 phases: 1) the development of a diagnostic tool for misconceptions in educational research problem formulation, 2) the diagnosis of graduate students’ misconceptions in educational research problem formulation, and 3) the development of activities for correcting the misconceptions. The samples were 152 Thai graduate students from faculties of education in 8 universities by stratified random sampling to participate in Phase 2. Based on results in Phase 2, fifteen graduate students who had misconceptions in educational research problem formulation were participants in Phase 3. The research tools were a three-tier multiple choice diagnostic test of problem formulation, a test for post-correcting misconception activity, a recording form for participants’ behaviors, and activity plans for correcting misconceptions in problem formulation. Data were analyzed by using descriptive statistics and t-test for dependent samples. The research findings were as follows: 1) The developed instrument for diagnosing misconceptions in educational research problem formulation was a set of 32 questions in forms of a three-tier multiple choice diagnostic test, covering 11 issues related to the research problem formulation. The quality examination revealed that the test has a satisfactory levels of content validity with IOCs between .67-1.00. In addition, the first and second tiers of the test have high levels of internal consistency as shown by KR-20 of .85 and .81, respectively. Difficulty levels range between 0.20-0.78, while discrimination levels range between 0.20-0.74. 2) The results of the diagnosis of misconceptions in educational research problem formulation showed that, overall, there were 45.94% of graduate students possessing misconceptions. The content that graduate students had the most misconception was the identification of keywords for searching information, whereas the identification of key issues was the least misconception. 3) The activities for correcting misconceptions in educational research problem formulation consists of 6 stages: 1) commit to an outcome, 2) expose beliefs, 3) confront beliefs, 4) accommodate the concept, 5) extend the concept, 6) go beyond. After participated in the activities, the participants had high scores in correct concepts and the score difference between pre- and post-tests was statistically significance at .05 level.